The influence of administrative thinking in knowledge management and innovation: a systematic review - Darwin Daniel Ordoñez Iturralde (Tendencias)
Introduction: This study examines how management thinking approaches can be integrated into knowledge management in order to promote innovation and improve operational efficiency in contemporary organizations. Objective: To analyze management strategies that optimize the use of organizational knowledge and highlight its impact on innovation and business performance. Methodology: A systematic literature review was conducted using the PRISMA method, collecting studies published between 2019 and 2023 in ScienceDirect, SpringerLink and Emerald Insight databases. Twenty-seven articles exploring the relationship between management thinking, knowledge management, innovation and operational efficiency were selected. Results: Findings show that collaborative strategies, such as communities of practice and learning, facilitate knowledge creation and transfer; while technological tools, such as knowledge management systems and data analytics, optimize decision making and improve operational efficiency.Conclusions: The integration of administrative approaches with advanced technologies enables organizations to increase their adaptability, foster continuous innovation and achieve greater operational efficiency. This highlights the need to promote a collaborative culture and invest in technologies that enhance the flow of organizational knowledge in order to ensure sustainable and competitive performance.